Pedampingan dan Pelatihan dalam Pembuatan Buku Ajar bagi Tenaga Pengajar di Rumah Belajar PATMOS dalam Meningkatkan Literasi Membaca Anak Pinggiran Rel Kereta Api - Lois Oinike Tambunan; Yoel Octobe Purba; Ria Retno Dewi Sartika Manik (Departement of Mathematics Education, 2024)
Writing textbooks is a skill that teachers should have to improve their professionalism. Teacher textbooks can be published and marketed in various formats. However, not many teachers are interested in writing textbooks. Several factors that hinder teacher motivation in writing textbooks include teachers' lack of understanding of book writing techniques, lack of ideas, and lack of free time. To overcome this, training in textbook preparation techniques is needed. This training and writing assistance will be provided by people who have experience making textbooks. The textbook writing training program consists of several activities, including socialization about textbook creation, training in textbook creation, mentoring in textbook creation and evaluation of the results of the training and mentoring. The aim of this PKM is to provide insight and skills in writing textbooks through training and assistance in writing textbooks for teachers or teaching staff at PATMOS learning homes. Apart from that, the results of this training produce textbook products that will be used in the PATMOS Learning home learning process with the hope of increasing children's reading literacy.